INCIDENTAL VOCABULARY ACQUISITION THROUGH HIDDEN OBJECT GAMES: A STUDY ON EFL LEARNERS' PERCEPTIONS OF CRIMINAL CASE - Galuh Fitriana Sakti; Defi Khusnul Khotimah; Edy Supriyanto (Universitas HKBP Nommensen, 2026)
This qualitative narrative study examines the perspectives of English as a Foreign Language (EFL) learners about the smartphone game Criminal Case as a mechanism for accidental English vocabulary learning. Despite the increasing prevalence of game-based learning, research on EFL learners' opinions towards commercially available games for vocabulary acquisition remains few. This study examines how 10 EFL learners evaluate the game's capacity to enhance vocabulary learning through its interactive hidden-object gameplay, visually stimulating locations, and contextualized language demands. Data obtained through interviews, and open-ended surveys indicate generally favorable perceptions, carefully classified into two primary dimensions: pedagogical and psychological. Educational perspectives highlight the game's ability to enhance vocabulary, support learning through visual aids, and serve as an additional resource for practical language exposure. Simultaneously, psychological perceptions underscore the game's motivating, engaging, and pleasurable attributes, which foster prolonged player interaction and objective-oriented learning. The study concludes that Criminal Case serves as a highly effective, interesting, and academically valid additional resource for vocabulary acquisition in EFL contexts. This study enhances the literature by offering comprehensive qualitative evidence that recommends for the integration of particular commercial games into EFL curriculum, positing game-based learning as a method to improve vocabulary retention and student motivation.